Theory and application of intermediate microeconomics - Walter Nicholson (Thomson Business and Economics, 2007)
Provides an introduction to the economic study of markets, focusing on managerial and algebraic approaches. This title is filled with examples and activities that allow students to learn by doing. It covers game theory, asymmetric information, and imperfect markets